PENGARUH STATUS GIZI TERHADAP KEJADIAN HIPERGLIKEMIA PADA PEGAWAI NEGERI SIPIL: STUDI KASUS DI KOTA DEPOK TAHUN 2009 - Rahmawati .; Asih Setiarini; Sudikno . (GIZI INDONESIA, 2009)
NFLUENCE OF NUTRITIONAL STATUS ON HYPERGLYCEMIA INCIDENCE AMONG THEGOVERNMENT EMPLOYEES: A CASE STUDY IN DEPOK CITY, 2009Several studies have shown an increasing trend of diabetes mellitus in Depok city. The objective ofthe study is to determine association of nutritional status on hyperglycemia incidence among thegovernment employees in Depok city. The study used case-control design covering 47 cases and 94controls, conducted between March – May 2009. Criteria for inclusion is government employees age40 year old or above, fasting blood glucose is 126 mg/dl for case and ≤ 126 for control group.Variabel collected for the study are fasting blood glucose, weight, height, socio-demographiccharacteristics, food consumption pattern and blood pressure. Bivariate (Chi-square test) andmultivariate (logistic regression) analysis were used to determine the association. The results revealthat hyperglycemia is significantly (p0,05) associated with body mass index (BMI) and family historyof hyperglycemia after controlling confounding factor of protein consumption. The risk ofhyperglycemia is 5,06 times among subjects with BMI ≥ 25,1 and 6,63 times among subjects withfamily history of hyperglycemia.Keywords: nutritional status, body mass index, hyperglycemiaqqqqqqqqqqqqq